2021
DOI: 10.17762/turcomat.v12i3.995
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies on Software Refactoring Techniques in the Industrial Setting

Abstract: Software refactoring is an approach that aims to improve software system quality by restructuring its internal design without altering the functionality of the software system. The software refactoring has gained comprehensive attention from the research community in software engineering since its emerging in 1999. Empirical studies were carried out to investigate whether the software refactoring indeed can achieve improvement in the software system quality. It is widely believed that refactoring has a favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To classify refactoring methods according to certain software quality characteristics, studies [35,44] exclusively utilized the refactoring methods for small software systems at the level of classes. As a consequence, they suggested that the usage of the small-size system may be an issue when examining how refactoring methods affect the system level [31,35,44,45]. Refactoring methods were utilized at the class level by Kumari and Saha [46], who highlighted that outcomes may vary when used at the system level.…”
Section: B Software Sizementioning
confidence: 99%
See 1 more Smart Citation
“…To classify refactoring methods according to certain software quality characteristics, studies [35,44] exclusively utilized the refactoring methods for small software systems at the level of classes. As a consequence, they suggested that the usage of the small-size system may be an issue when examining how refactoring methods affect the system level [31,35,44,45]. Refactoring methods were utilized at the class level by Kumari and Saha [46], who highlighted that outcomes may vary when used at the system level.…”
Section: B Software Sizementioning
confidence: 99%
“…• Refactoring methods have a mixed impact on software quality [30][31][32]. Several studies have discovered that different refactoring methods have varying and distinct effects on software quality characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the most commonly employed refactoring techniques, an extensive review and analysis of existing literature were conducted in this study. Notably, five systematic literature reviews [13], [30], [48], [49], [50] and one systematic mapping study [31] identified frequently utilized refactoring techniques within academic research. In addition, Kim et al [15], [51] identified prevalent refactoring techniques employed in the software engineering practices at Microsoft.…”
Section: ) Identifying the Refactoring Techniquesmentioning
confidence: 99%
“…To enhance the internal structure of a software system, refactoring has been deployed. This involves the alteration of the software system in such a manner that it does not alter the external behavior of the code but improves its internal structure [53]. It is an effective tool used to enhance the quality of software, such as maintainability, testability, and understandability.…”
Section: Techniques Geared Towards Software Securitymentioning
confidence: 99%
“…Recent studies showed that the effects of refactoring techniques on software quality attributes are inconsistent and contradictory [164]. As pointed out in [165] and [53], the inconsistent or contradictory results concerning the effect of refactoring techniques [166] on software quality, is one of the challenges for developers when they use the refactoring techniques to improve software quality. As such, categorization of the refactoring techniques based on their effect on software quality attributes can potentially help developers in achieving their design objectives.…”
Section: Challenges In Implementing Software Securitymentioning
confidence: 99%